Analysis of Chemical Traits of Pollen from Nine Ericaceous Species in Southwestern China - Xiaoyue Wang; Jianghu Wang; Shunyu Wang; Yang Li; Haifeng Xu; Yin Yi; Xiaoxin Tang (Horticulturae)
Chemical traits (primary and secondary metabolites) are important features of plants. An increasing number of studies have focused on the ecological significance of secondary metabolites in plant parts, especially in pollen. Ericaceae species exhibit significant morphological variations and diverse colors, are widely distributed throughout China and are popular ornamental garden plants. The chemical trait of pollen in Ericaceae species and their potential ecological significance remain unclear. We selected a total of nine Ericaceae species from three nature reserves in southwestern China, which were the predominant flowering Ericaceae plants for each site, and measured their floral characteristics, nectar volume and sugar concentration. We determined the types of pollinators of these species based on a literature review and used UPLC-QTOF-MS to analyze the types and relative contents of primary metabolites (amino acids and fatty acids) and secondary metabolites (terpenoids, phenolics and nitrogenous compounds) in the pollen and other tissues, including the stems, leaves, petals and nectar. The results showed that each species exhibited unique floral characteristics. Enkianthus ruber, Pieris formosa, Rhododendron agastum, R. irroratum, R. virgatum and R. rubiginosum were pollinated by bees, and R. delavayi, R. decorum and R. excellens were pollinated by diverse animals (bees, birds and Lepidoptera). The pollen of these Ericaceae species was rich in phenolics and terpenoids, especially flavonoids. Grayanotoxin, andromedotoxin and asebotin (toxic diterpene compounds) were also detected in the pollen of some of the Ericaceae species in our study, and their response value was low. The relative contents and diversity of secondary metabolites in the pollen were higher than those in the nectar but lower than those in the leaves, petals and stems. The five chemical compounds with the highest content (four flavonoids, one triterpene) in the pollen were also detected in the stems, leaves and petals, and the response value of most of these chemicals in pollen was not significantly correlated with that in other tissues. Rhododendron species has a closer relationship with chemical traits in pollen compared with Enkianthus and Pieris species. The response value of total secondary metabolites in the pollen of species pollinated only by bees was higher than that of species pollinated by diverse animals. Our research indicates that the pollen of ericaceous species contains a wide array of metabolites, establishing a foundation for advancing the nutritional potential of the pollen of horticultural ericaceous species and deepening our understanding of its chemical and ecological significance.